Cover Feature: Magnesium Reagents Featuring a 1, 1′‐Bis(o‐carborane) Ligand Platform (Eur. J. Inorg. Chem. 38‐39/2017). Issue 38 (4th October 2017) - Axtell, Jonathan C.; Kirlikovali, Kent O.; Dziedzic, Rafal M.; Gembicky, Milan; Rheingold, Arnold L.; Spokoyny, Alexander M.
Abstract : The Cover Feature shows a simple combination of a bis( o ‐carborane) and a magnesium source facilitating the synthesis of a Grignard‐type bis( o ‐carborane) delivery system. The bis( o ‐carboranyl)magnesiate, which is an isolable powder and a solid that is stable under an inert atmosphere for months, functions to transfer the bis( o ‐carboranyl) ligand to main group electrophiles such as tin. The open road in the background represents the untapped potential and avenues for application that remain open for this reagent in organometallic, main group, and organic chemistry. (Cover art designed by Alex I. Wixtrom). More information can be found in theCommunication by J. C. Axtell, A. M. Spokoyny et al.